Sikap Syekh Nawawi al-Bantani Terhadap Kolonialisme Belanda dalam Tafsir Marāḥ Labīd - Taryudi Taryudi; Dadan Rusmana; Muhamad Yoga Firdaus (Jurnal Penelitian Ilmu Ushuluddin, 2026)
This study examines the attitude of Shaykh Nawawi al-Bantani toward Dutch colonialism as reflected in his interpretation of the qitāl (warfare) verses in Tafsir Marāḥ Labīd. This research employs a qualitative approach based on library research using the thematic (maudhū‘i) method of Qur’anic interpretation. The analytical framework refers to the classification of qitāl verses proposed by Mahmud Syaltut, particularly those related to the relationship between Muslims and non-Muslims. The analysis focuses on Shaykh Nawawi’s interpretation of Q.S. al-Hajj (22):39–41 and Q.S. al-Baqarah (2):190–194. The findings indicate that Shaykh Nawawi understands warfare in the Qur’an as a defensive act aimed at responding to oppression and protecting religious freedom, while emphasizing ethical limitations in conflict. Although his interpretation does not explicitly connect the qitāl verses with Dutch colonialism, it can be understood within the intellectual-historical context of the nineteenth century as reflecting a religious stance that tends to be non-confrontational yet critical of oppression, particularly through the strengthening of Islamic scholarly traditions and intellectual networks in the Nusantara.